2021
DOI: 10.32412/pjohns.v36i1.1631
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anosmia and Positive SARS-CoV-2 (COVID-19) RT-PCR Test Results Among Patients in the Quezon City General Hospital

Abstract: ABSTRACT Objective: To determine the association of anosmia and positive SARS-CoV-2 (COVID-19) RT-PCR test results among patients in a tertiary government hospital in Metro Manila.   Methods: Design: Cross-Sectional Study Setting: Tertiary Government Hospital Participants: Patients aged 18 years old and above who consulted or were admitted with COVID-19 symptoms at the Quezon City General Hospital in the Philippines from July to September 2020 answered an offline version of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…In summary, our study revealed a high prevalence of anosmia in confirmed COVID-19 patients in consonance with other reports [6][7][8][17][18] with a good percentage of patients recovering from anosmia spontaneously. The majority of COVID-19 patients with anosmia had minimal or negligible impairment, while a small percentage had impaired quality of life.…”
Section: Original Articlessupporting
confidence: 92%
See 2 more Smart Citations
“…In summary, our study revealed a high prevalence of anosmia in confirmed COVID-19 patients in consonance with other reports [6][7][8][17][18] with a good percentage of patients recovering from anosmia spontaneously. The majority of COVID-19 patients with anosmia had minimal or negligible impairment, while a small percentage had impaired quality of life.…”
Section: Original Articlessupporting
confidence: 92%
“…13 The prevalence of anosmia in patients with COVID-19 infection ranges from 5 to 26, 32, 35, 48, and 79 percent. [7][8][14][15][16] Alega and Cruz reported that 51% (60/117) of COVID-19 positive individuals reported loss of smell 8 while Regalado et al reported an overall prevalence of 71% in a systematic review. 18 The prevalence rate of 66% in our present study is consonant with other reports that anosmia is associated with COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation